Clinical significance and importance of elevated urinary kryptopyrroles (UKP): Self-reported observations and experience of Australian clinicians using UKP testing. Issue 3 (September 2021) - Rainforest, Jason; Schloss, Janet; Foley, Hope; Steel, Amie
Highlights: Research has linked urinary levels of kryptopyrroles (UKP) to psychiatric illness since the 1960s. There is uncertainty regarding the epidemiology, diagnosis, management and prognosis of patients with elevated UKP. Anecdotal evidence suggests clinicians are attempting to manage elevated UKP levels in their patients. Clinicians that test UKP prescribe nutritional products, and diet and lifestyle changes to reduce elevated UKP levels. Clinicians that test UKP observe mood swings, social withdrawal, and compulsive behaviour among patients with elevated UKP. Abstract: Introduction: Urinary kryptopyrroles (UKP), or the 'Mauve factor', was first described in the early 1960s with an observed association with psychiatric illness. Since this time, there has been growing interest in the clinical importance of UKP testing for a range of clinical conditions. However, there are substantive gaps in the available evidence to inform appropriate application and interpretation of UKP tests. With this in mind, this study describes the observed health conditions, treatments and diagnostic application of UKP by clinicians using it within their clinical practice. Methods: Observational cross-sectional self-report online survey of Australian clinicians, recruited through a company that provides functional testing (including UKP analysis), who identify as having used UKP testing within their clinical practice. The survey collected data on participant demography and characteristics of their clinical practice, their approach to the diagnosis and interventions used to clinically manage elevated UKP (eUKP), and the observed clinical importance of eUKP for a range of health conditions. Results: The survey was completed by 86 respondents. The majority of participants used nutritional supplements (76.7%), dietary therapy (60.5%) and lifestyle changes (58.1%) to clinically manage eUKP. Nervous system (86.0%) and gastrointestinal (64.0%) conditions were most commonly observed by respondents to be linked to eUKP. Anxiety was observed by 91.9% of respondents to be associated with eUKP and was also the condition most commonly described as markedly improving following treatment of eUKP. A number of factors were reported to be associated with eUKP by the majority of respondents including mood swings (100%), social withdrawal (92.5%), compulsive behaviour (82.4%) and emotional eating (77.8%). Implications: Given the substantive gaps in evidence associated with UKP testing, this data may provide direction for researchers to design projects that reflect UKP testing as it is used in grass-roots clinical practice.